THE IMPORTANCE OF NONFORMAL EDUCATION ON CHILDREN 10-12 YEARS OLD - Andrieş Vasile; Onesim Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Non-formal education, created by different means in the education of children aged 11-12, plays a very important role in the implementation of the education process, as we know it. By using this adjacent means of education, we hope that students will practice physical exercises in a more unitary and greater way than they used to.